The Efficacy of the Interferon Alpha/Beta Response versus Arboviruses Is Temperature Dependent - Whitney C. Lane; Matthew D. Dunn; Christina L. Gardner; L. K. Metthew Lam; Alan M. Watson; Amy L. Hartman; Kate D. Ryman; William B. Klimstra (mBio, 2018)
ABSTRACT Interferon alpha/beta (IFN-α/β) is a critical mediator of protection against most viruses, with host survival frequently impossible in its absence. Many studies have investigated the pathways involved in the induction of IFN-α/β after virus infection and the resultant upregulation of antiviral IFN-stimulated genes (ISGs) through IFN-α/β receptor complex signaling. However, other than examining the effects of genetic deletion of induction or effector pathway components, little is known regarding the functionality of these responses in intact hosts and whether host genetic or environmental factors might influence their potency. Here, we demonstrate that the IFN-α/β response against multiple arthropod-vectored viruses, which replicate over a wide temperature range, is extremely sensitive to fluctuations in temperature, exhibiting reduced antiviral efficacy at subnormal cellular temperatures and increased efficacy at supranormal temperatures. The effect involves both IFN-α/β and ISG upregulation pathways with a major aspect of altered potency reflecting highly temperature-dependent transcription of IFN response genes that leads to altered IFN-α/β and ISG protein levels. Discordantly, signaling steps prior to transcription that were examined showed the opposite effect from gene transcription, with potentiation at low temperature and inhibition at high temperature. Finally, we demonstrate that by lowering the temperature of mice, chikungunya arbovirus replication and disease are exacerbated in an IFN-α/β-dependent manner. This finding raises the potential for use of hyperthermia as a therapeutic modality for viral infections and in other contexts such as antitumor therapy. The increased IFN-α/β efficacy at high temperatures may also reflect an innate immune-relevant aspect of the febrile response. IMPORTANCE The interferon alpha/beta (IFN-α/β) response is a first-line innate defense against arthropod-borne viruses (arboviruses). Arboviruses, such as chikungunya virus (CHIKV), can infect cells and replicate across a wide temperature range due to their replication in both mammalian/avian and arthropod hosts. Accordingly, these viruses can cause human disease in tissues regularly exposed to temperatures below the normal mammalian core temperature, 37°C. We questioned whether temperature variation could affect the efficacy of IFN-α/β responses against these viruses and help to explain some aspects of human disease manifestations. We observed that IFN-α/β efficacy was dramatically lower at subnormal temperatures and modestly enhanced at febrile temperatures, with the effects involving altered IFN-α/β response gene transcription but not IFN-α/β pathway signaling. These results provide insight into the functioning of the IFN-α/β response in vivo and suggest that temperature elevation may represent an immune-enhancing therapeutic modality for a wide variety of IFN-α/β-sensitive infections and pathologies.